Clinical manifestations of exuberant leishmaniasis mucocutaneous: case report (Research, Society and Development, 2022)
Cutaneous mucosal leishmaniasis (LM) is a chronic infection that affects the upper respiratory tract and/or buccal mucosa and is caused by Leishmania protozoan parasites. A 71-year-old male smoker received dental care at the Stomatology Service of the Hospital Metropolitano Odilon Behrens (HMOB), after various appointments with medical specialists. He presented granulomatous and erythematous lesions on the skin of the nose, on upper lip mucosa, and along the entire soft palate and uvula, as well as the destruction of the nasal septum. Due to the suspicion of leishmaniasis, an incisional biopsy was performed. Histopathological examination was performed; however, polymerase chain reaction (PCR) and immunofluorescence were necessary to confirm the diagnosis of LM. The patient was treated with 27 doses of liposomal amphotericin B 20mg / Sbv / kg / day. Due to the lack of improvement, the patient was again hospitalized, and the medication was repeated adding Fluconazol 150mg, to which the patient showed significant improvement. The present case report shows an infectious lesion that is unusual in dental practice and its approach. The description of the characteristics and management, together with the pathological process, were presented.